The Application of Z-Score and Zavgren Models in Managing Financial Distress at PT Garuda Indonesia (Persero) Tbk - Damayanti, Resma; Putri, Aulya (Research Collaboration Community (RCC), 2024)
As an archipelago, the aviation sector in Indonesia plays an important role, but PT Garuda Indonesia (Persero) Tbk. as one of the airline companies has experienced significant financial pressure. In the third quarter of 2023, the company recorded a net loss of US 72.07 million. This condition may put the company at risk of financial distress, a situation in which the company experiences financial difficulties before bankruptcy. This study uses the Altman Z-Score Model and the Zavgren Model to predict potential financial distress at PT Garuda Indonesia (Persero) Tbk. The analysis results show that from 2021 to 2023, the Altman Z-Score is consistently in the Bankrupt category, reflecting a high risk of bankruptcy, while the Zavgren model shows vulnerable conditions in 2021 but also indicates bankruptcy in 2022 and 2023. The results of this study are expected to provide early warning and assist management decision-making to reduce the risk of bankruptcy.